Short-term Changes in Health-related Quality of Life of Patients Undergoing Radical Surgery for Upper Urinary Tract Urothelial Carcinoma: Results from a Prospective Phase 2 Clinical Trial - van Doeveren, Thomas; Remmers, Sebastiaan; Atema, Vera; van den Bergh, Roderick C.N.; Boevé, Egbert R.; Cornel, Erik B.; van der Heijden, Antoine G.; Hendricksen, Kees; Cauberg, Evelyne C.C.; Jacobs, Rens A.L.; Kroon, Bin K.; Leliveld, Annemarie M.; et al. (European urology open science (Online), 2024)
A temporary decline in patient-reported health-related quality of life can be expected following radical surgery for upper tract urothelial carcinoma, with full recovery to presurgery levels 3 mo after surgery. The possible negative impact of radical surgery on patients’ health-related quality of life (HRQoL) plays an important role in preoperative counseling. Here, we analyzed the HRQoL of patients treated for upper urinary tract urothelial carcinoma (UTUC) in the context of a single-arm phase 2 multicenter study, in which the safety and efficacy of a single preoperative intravesical instillation with mitomycin C were investigated. Our objective was to investigate early changes in HRQoL in patients undergoing radical surgery for UTUC and identify factors associated with these outcomes. Patients with pTanyN0-1M0 UTUC were prospectively included. HRQoL was assessed using the European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire C30 (EORTC QLQ-C30) questionnaire at baseline, and at 1 and 3 mo after surgery. A linear mixed model was used to evaluate the changes in HRQoL over time and identify the variables associated with these outcomes. The clinical effect size was used to assess the clinical impact and level of perceptibility of HRQoL changes for clinicians and/or patients based on given thresholds. Between 2017 and 2020, 186 patients were included. At baseline, 1 mo after surgery, and 3 mo after surgery, response rates were 91%, 84%, and 78%, respectively. One month after surgery, a statistically significant and clinically relevant deterioration was observed in physical, role, and social functioning, and for the included symptom scales: constipation, fatigue, and pain. An improvement in emotional functioning was observed. At 3 mo, HRQoL returned to baseline levels, except emotional functioning, which improved at 1 mo and persisted to be better than that before surgery. Age >70 yr was associated with worse physical functioning, but better social and emotional functioning. Male patients reported better emotional functioning than females. Postoperative complications were negatively associated with social functioning. UTUC patients treated with radical surgery experienced a significant, albeit temporary, decline in HRQoL. Three months following surgery, HRQoL outcomes returned to baseline levels. This information can be used to counsel UTUC patients before undergoing radical surgery and contextualize recovery after surgery. We investigated the changes in quality of life as reported by patients who underwent surgery for upper tract urothelial carcinoma (UTUC). We found that patients experienced a decline in quality of life 1 mo after surgery, but this was temporary, with full recovery of quality of life 3 mo after surgery. These findings can help doctors and other medical staff in counseling UTUC patients before undergoing radical surgery.